(untitled) (Scientia Agricola, 2015)
Tillage and fertilization methods may affect soil fertility. With the aim of assessing changes in soil chemical properties over a period of ten years, soil samples of a Paleudult were collected over nine seasons at three layer depths (0-5, 5-10, 10-20 cm) and were chemically analyzed. Grain yield and nutrient export in two summer crops, soybean (Glycine max) and corn (Zea mays), in a field experiment set in Eldorado do Sul, in the state of Rio Grande do Sul, Brazil, were determined. Three soil tillage systems were evaluated, conventional (CT), reduced (RT) and no-tillage (NT), combined with mineral (lime and fertilizers) and organic (poultry litter) fertilization. The no-tillage system stood out as compared to the others, especially in the surface layer, in terms of values of organic matter, soil pH, available phosphorus, cation exchange capacity and base saturation. Phosphorus content was higher under organic than mineral fertilization due to the criteria used for the establishment of fertilizer doses. Under organic fertilization, soil pH values were similar to those obtained in limed soil samples because of the cumulative effect of the organic fertilizer. Soybean yield was lower under NT in comparison to the RT and CT systems. Consequently, soybean grain exported a lower content of nutrients than maize grain. Maize yield was not affected by either tillage or fertilization systems.